Tobacco smoking-response genes in blood and buccal cells. Issue 2 (22nd January 2015) - Na, Hyun-Kyung; Kim, Minju; Chang, Seong-Sil; Kim, Soo-Young; Park, Jong Y.; Chung, Myeon Woo; Yang, Mihi
Graphical abstract The most significant biological pathways for the set of smoking correlated genes: (A) the lists of the most enriched pathways which were categorized by KEGG pathways. (B) An integrative network of genes differentially expressed by 1.5-fold change in smokers, compared to nonsmokers.